Factors Affecting the Intention to Cash Waqf in Urban Muslims: an Extended Theory of Planned Behavior Approach - Asyari, Asyari Ari; Susanto, Perengki; Awaluddin, Awaluddin; Gunawan, Didik (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
This study investigates the factors influencing intention for cash waqf participation among urban Muslims. Drawing from the Theory of Planned Behavior (TPB) and incorporates the factor of knowledge of Islamic ownership, it collected data from 449 respondents from two cities in West Sumatra, Padang and Bukittinggi and analyzed. through Smart PLS 4.0. The results disclose that three TPB variables—attitude, subjective norms, and perceived behavior control—and knowledge of Islamic ownership exert a positive and statistically significant influence on the intention to cash waqf among urban Muslims. It underscores the importance of recognizing knowledge of Islamic ownership as a determinant variable in the intention to engage in cash waqf. Cash waqf management institutions should prioritize cultivating a positive image, ensuring convenience, and offering tangible benefits to cash waqf contributors. Moreover, the active involvement of religious and social leaders is essential for optimizing the collection of cash waqf funds. Abstrak. Studi ini menyelidiki faktor-faktor yang mempengaruhi niat berpartisipasi wakaf tunai di kalangan Muslim perkotaan. Berangkat dari Teori Perilaku Terencana (TPB) dan memasukkan faktor pengetahuan kepemilikan Islam, penelitian ini mengumpulkan data dari 449 responden dari dua kota di Sumatera Barat, Padang dan Bukittinggi dan dianalisis. melalui Smart PLS 4.0. Hasil penelitian menunjukkan bahwa tiga variabel TPB—sikap, norma subjektif, dan kontrol perilaku yang dirasakan—dan pengetahuan tentang kepemilikan Islam memberikan pengaruh positif dan signifikan secara statistik terhadap niat wakaf uang di kalangan umat Islam perkotaan. Hal ini menggarisbawahi pentingnyamerekognisii pengetahuan tentang kepemilikan Islam sebagai variabel penentu niat untuk berwakaf uang. Lembaga pengelola wakaf tunai harus mengedepankan penanaman citra positif, kenyamanan, dan manfaat nyata bagi para pendonor wakaf tunai. Selain itu, keterlibatan aktif tokoh agama dan tokoh masyarakat juga penting untuk mengoptimalkan penghimpunan dana wakaf tunai.